2019
DOI: 10.1093/biolre/ioz130
|View full text |Cite
|
Sign up to set email alerts
|

Inosine RNA modifications are enriched at the codon wobble position in mouse oocytes and eggs†

Abstract: Mammalian oocytes and eggs are transcriptionally quiescent and depend on post-transcriptional mechanisms for proper maturation. Post-transcriptional mRNA modifications comprise an important regulatory mechanism that can alter protein and miRNA recognition sites, splicing, stability, secondary structure, and protein coding. We discovered that fully grown mouse germinal vesicle oocytes and metaphase II eggs display abundant inosine mRNA modifications compared to growing oocytes from postnatal day 12 oocytes. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 90 publications
4
21
0
Order By: Relevance
“…It has recently been reported that inosine RNA modifications in the coding sequence of mRNA lead to ribosome stalling (Licht et al 2019). In a previous report (Brachova et al 2019), and now here in WT and Btg4 -/oocytes, we identified inosine RNA modifications specifically enriched in at the codon wobble position in oocytes (Brachova et al 2019). Based on our finding and others, we hypothesized that inosine RNA modifications within the coding sequence could alter mRNA stability, potentially through translational mRNA decay.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has recently been reported that inosine RNA modifications in the coding sequence of mRNA lead to ribosome stalling (Licht et al 2019). In a previous report (Brachova et al 2019), and now here in WT and Btg4 -/oocytes, we identified inosine RNA modifications specifically enriched in at the codon wobble position in oocytes (Brachova et al 2019). Based on our finding and others, we hypothesized that inosine RNA modifications within the coding sequence could alter mRNA stability, potentially through translational mRNA decay.…”
Section: Discussionsupporting
confidence: 78%
“…Inosine RNA modifications are lost in oocytes from Cnot6l -/mice Using our computational approach (Brachova et al 2019), we identified transcriptome wide inosine RNA modifications (Supplemental Fig. S1) in previously reported RNA-seq datasets (Sha et al 2018) from wild-type (WT), Cnot6l -/-, Btg4 -/oocytes at 0, 8, and 16 h after in vitro maturation.…”
Section: Resultsmentioning
confidence: 99%
“…Inosine RNA modifications are identified by comparing the transcriptome to the genome to identify A-to-G mismatches, as we and others have shown [ 28 , 30 , 31 , 32 ]. Using our computational approach [ 28 ], we identified transcriptome-wide inosine RNA modifications ( Supplemental Figure S1 ) in previously reported RNA-seq datasets [ 14 ] from wild-type (WT), Cnot6l -/- , and Btg4 -/- oocytes and eggs at 0, 8, and 16 h after in vitro maturation. These three time points correspond to the GV, MI, and MII oocyte and egg stages, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study linked inosine RNA modifications to the process of translation through RNA modifications of codons [ 28 ]. To test if the accumulated and over-translated maternal transcripts found in oocytes/eggs of Cnot6l -/- mice were enriched in inosine RNA modifications, we cataloged inosine RNA modifications in ribosome-associated mRNA (i.e., mRNA bound by multiple ribosomes) at the GV, MI, and MII stages in WT and Cnot6l -/- oocytes/eggs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation